THE IMPLEMENTATION OF THE MULTIMEDIA APPROACH TO TEACHING BUSINESS ENGLISH - Olena Karpova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The paper deals with the problem of using multimedia technologies in teaching Business English at higher educational establishments. Modern forms, methods, and techniques of teaching Business English with multimedia tools have been considered. The author has outlined the components of the multimedia approach, its peculiarities and ways of using it in the classroom. Such methods of research as questionnaires, tests, quizzes, the pedagogical experiment and methods of mathematical statistics have been used. The author defines the multimedia technology as a type of a pedagogical technology that implies such organisation of an educational process that combines common forms, teaching methods and techniques with multimedia tools and products. Interactive methods and techniques, multimedia tools and multimedia products have been distinguished as the components of the introduced multimedia approach to teaching Business English. The results of the experiment have proved the efficacy of the implementation of the multimedia approach to teaching Business English at a higher educational establishment especially due to decreasing credits on obligatory disciplines and increasing hours given to out-of-class individual work of students.